2013
DOI: 10.1186/2193-1801-2-141
|View full text |Cite
|
Sign up to set email alerts
|

The role of quality control circles in sustained improvement of medical quality

Abstract: We used quality control circles (QCC) followed by the PDCA Deming cycle and analyzed the application of QCC to the sustained improvement of a medical institution in Zhejiang province. Analyses of the tangible and intangible achievements of QCC revealed that the achievement indices for reductions in internal errors, reductions in costs, improvements in the degree of patient satisfaction, improvements in work quality, and improvements in economic performance were 109.84% ± 16.47%, 135.04% ± 50.33%, 126.26% ± 53.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 5 publications
1
39
0
2
Order By: Relevance
“…Given that patients' needs are constantly changing in healthcare organizations, employees need to update their knowledge to accommodate these changes; in this, employee training can play an important role. In the current study, 'Clear goals and objectives' was found to be the third factor influencing the effectiveness of QCCs, which is confirmed by the results of the studies by Wang et al 13 and Welekar. 42 Also, 'Voluntary membership', 'Using the right tools', 'Group cohesiveness and homogeneity', 'Reward system', 'Feedback system', 'Organizational culture', 'Management style', 'Regularly holding meetings' and 'Group leadership' were other effective factors, which is consistent with the results of Jiang et al 43 and Mahlknecht et al 44 Sharif and Irani 45 have also considered 'Group leadership' as a crucial factor for focusing on creating and maintaining the internal environment, and believe that paying more attention to the development of appropriate leadership styles in the organization can lead to the survival and improvement of the supply chains and performance management.…”
Section: Discussionsupporting
confidence: 88%
“…Given that patients' needs are constantly changing in healthcare organizations, employees need to update their knowledge to accommodate these changes; in this, employee training can play an important role. In the current study, 'Clear goals and objectives' was found to be the third factor influencing the effectiveness of QCCs, which is confirmed by the results of the studies by Wang et al 13 and Welekar. 42 Also, 'Voluntary membership', 'Using the right tools', 'Group cohesiveness and homogeneity', 'Reward system', 'Feedback system', 'Organizational culture', 'Management style', 'Regularly holding meetings' and 'Group leadership' were other effective factors, which is consistent with the results of Jiang et al 43 and Mahlknecht et al 44 Sharif and Irani 45 have also considered 'Group leadership' as a crucial factor for focusing on creating and maintaining the internal environment, and believe that paying more attention to the development of appropriate leadership styles in the organization can lead to the survival and improvement of the supply chains and performance management.…”
Section: Discussionsupporting
confidence: 88%
“…The QCC program was launched based on the QCC theory [12], and the basic steps of QCC program were outlined in Additional file 1. The roles of QCC program included project director, counselor, circle head and circle members, which were acted by infection control officer, charge nurse, department head and the rest dentists and nurses, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Cyklický model PDCA, ktorý je základným pilierom manažmentu kvality, sa uplatňuje aj pri procesoch popisujúcich starostlivosť o pacientov [20]. Demingov model je celosvetovo uznávaný, čo potvrdzuje jeho uplatniteľnosť v zahraničí pri trvalom zlepšovaní kvality zdravotníckeho zariadenia [21].…”
Section: Diskusiaunclassified